THE RENEWAL OF THE EVIDENTIARY PROCESS FOR THE CRIMINAL ACT OF SUPERNATURAL PRACTICES - Meitria Cahyani; Febrian Arif Wicaksana; Andini Rachmawati; Fazari Zul Hasmi Kanggas; Aisyah Habibah Rahman (Journal of Indonesian Comparative of Syari'ah Law, 2025)
The practice of supernatural rituals in Indonesia continues despite advancements in science and technology, with various cases of fraud and abuse harming society, such as the cases involving shamans in Sukabumi and Yono. To address this issue, the government has regulated it under Article 252 of the 2023 Criminal Code (KUHP), which will take effect in 2026, aiming to curb harmful practices and prevent vigilante actions, although challenges in proving such offenses remain a major obstacle. This study employs a normative juridical approach, utilizing legal analysis and literature review methods related to evidentiary law in criminal offenses. Additionally, it examines the legal framework surrounding supernatural practices as a criminal act and how evidence is established under Article 252 of Law Number 1 of 2023 concerning the Criminal Code. The findings reveal that shamanic offenses were previously regulated under Articles 545 to 547 of the existing Criminal Code, but these provisions have been found inadequate in addressing harmful supernatural practices and fail to provide a deterrent effect due to lenient penalties.